Design of fractional order controller for a servohydraulic positioning system with micro artificial bee colony algorithm - Rajasekhar, Anguluri. (2013)
This paper deals with an interesting application of designing a Fractional Order Controller for a Servo hydraulic positioning system, to compensate the negative effects of fluid leakage across a faulty actuator piston seal. A novel micro artificial bee colony algorithm (μABC) has been proposed for designing this Fractional order Controller based on minimizing Integral Time Absolute Error (ITAE) criterion. As μABC requires a less number of bees, the solution is obtained much faster than that of basic Artificial Bee Colony (ABC) method. Simulations and comparisons of proposed method along with that of GA and an adaptive variant of ABC in terms of time domain indices indicate the superiority of μABC in designing the fractional controller for a much complex plant.